Stereochemistry of 2,6-Diaminoadamantane salts: transannular interactions - Glaser, Robert; Steinberg, Avital; Šekutor, Marina; Rominger, Frank; Trapp, Oliver; Mlinarić-Majerski, Kata (European journal of organic chemistry, 2011)
A series of bisprimary, bistertiary, and bisquaternary adamantane-2,6-diammonium salts were synthesized from adamantane-2,6-dione starting material. Conversion of the dione to a dioxime followed by H2/PtO2 hydrogenation afforded 2,6-diaminoadamantane dihydrochloride 2a. Reductiveamination of 2a with aqueous formaldehyde (H2/PtO2) gave rac-N,N,N′,N′-tetramethyl-2,6-diaminoadamantane dihydrochloride salt 3. Diffusion of acetone into a solution of 3 in methanol gave 2.5 hydrate crystals in a triclinic P$\bar 1$ cell, which had two molecules of opposite handedness and five water molecules in the asymmetric unit. Diamine 2a with excess CH3I yielded rac-N,N,N,N′,N′,N′-hexamethyladamantane-2,6-diaminium diiodide quaternary salt 4a. Diiodide 4a with molecular bromine gave the corresponding dibromide 4b. Acetone diffusion into a solution of 4a (or 4b) in methanol gave isostructural monohydrate crystals in orthorhombic Pnma cells. An enantiomeric pair of 4a,4b (2RS,6RS)-diaminium ions is disordered about the mirror plane, since chiral cation occupancy of this location requires symmetry that cannot be fulfilled. In solution, all the cations had C2 symmetry, as detected by NMR spectroscopy, whereas an approximate C2 symmetry was observed in crystals. RmS(G) quantification of crystallographic pseudo-symmetry shows high fidelity for pseudo-inversion symmetry between cations of opposite handedness in crystal 3, and for pseudo-C2 symmetry within adamantane skeletons of crystals 3, 4a, and 4b. Axial NMe3 or NHMe2 groups on adamantane-2 (or -6-)-positions suffer cis-1,3-diaxial repulsion, very similar to that involving axial tBu or iPr groups and H(axial) protons on cyclohexane. These transannular steric interactions tilt the NMe3 units outward by about 19°, while NHMe2 groups slant outward by a smaller and more usual 7°.
Gesehen am 24.06.2022